Pyruvate Kinase M2: Regulatory Circuits and Potential for Therapeutic Intervention - Gupta, Vibhor; E. Wellen, Kathryn; Mazurek, Sybille; K. Bamezai, Rameshwar N. (Current Pharmaceutical Design, 2014)
Cancer cells are characterized by reprogramming of energy metabolism. Over the last decade, understanding of the metabolic changes that occur in cancer has increased dramatically, with great interest in targeting metabolism for cancer therapy. Pyruvate kinase isoenzyme type M2 (abbreviations: PKM2, M2-PK) plays a key role in modulating glucose metabolism to support cell proliferation. PKM2, like other PK isoforms, catalyzes the last energy-generating step in glycolysis, but is unique in its capacity to be regulated. PKM2 is regulated at several cellular levels, including gene expression, alternative splicing and post-translational modification. In addition, PKM2 is regulated by key metabolic intermediates and interacts with more than twenty different proteins. Hence, this isoenzyme is an important regulator of glycolysis, and additionally functions in other novel roles that have recently emerged. Recent evidence indicates that intervening with the complex regulatory network of PKM2 has severe consequences on tumor cell proliferation, indicating the potential of this enzyme as a target for tumor therapy.
Keywords: alternative splicing